Social Media/Networking: Applications, Technologies, Theories - Madakam, Somayya; Tripathi, Siddharth (Journal of Information Systems and Technology Management, 2021)
Nowadays, Social Media communication has become indispensable for the world. Social Media is indeed a paradigm shift in communication. The beauty of this new communication method is the offer of virtual connectivity irrespective of geographical distances. The medium serves us 24/7 with online videos, audios, pictures, and rich textual content. Given its wide usage, it is extremely crucial to study key details of social media, including the pioneers, theories, and business applications. This manuscript has relied on the “Web of Science” database and the Vantage Point 9 text-mining tool, with Aduna map visualization, to collate about 50 research articles published during 2008-2016 that have studied social media in detail. The objective of this article is to explain the impact of social media sites, technologies and applications.